Analysis of the Contents of the Cleanliness Campaign in the Kompas TV article “Blitar Police Car Turned into a Mask Waste Bank” - Sari, Yoana Puspita; Savitri, Hikmawati Fadjri Devi (Prosiding University Research Colloquium, 2021)
The The COVID-19 pandemic requires people to comply with health protocols, one of which is wearing a mask. The use of masks is part of a comprehensive series of prevention and control measures that can limit the spread of the virus. The increasing amount of mask waste and the absence of waste management have a negative impact on environmental hygiene and health. Seeing this case, it is necessary to carry out a mask waste management campaign. The purpose of this study was to analyze the contents of the hygiene campaign in the Kompas TV article "Blitar Police Car Turned into a Mask Waste Bank". This study uses a qualitative content analysis method. Data collection techniques through primary data collection from literature studies through journals, articles, and news. The data analysis technique used content analysis techniques. The results of the study are in the form of content analysis on the contents of the Kompas TV article cleanliness campaign "Blitar Police Car Turned into a Mask Waste Bank", in the form of different sentence elements in it. This is a hygiene campaign that is being pursued as an effort to reduce the amount of APD waste, especially masks that are scattered and thrown away carelessly..